From the history of the establishment of reserves on the territory of uzbekistan. - Olimov Jahongir Boriboevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article discusses the establishment of reserves on the territory of Uzbekistan, and the maintenance of reserves by Rare Plants rare in nature, as well as animals, which serve to preserve attractive nature in their own way.